Potret Model Kegiatan Berbahasa Arab Bagi Santri Pesantren Modern al-Amanah, Sidoarjo Indonesia - Rochmawati, Nur; Taufiq, Mirwan Akhmad; Romdlon, Atiq Mohammad (Program Studi Pendidikan Bahasa Arab, 2025)
This study aims to identify models of activities that can enhance Arabic language skills at the al-Amanah Islamic Boarding School. The objective is to explore the types of language activities that strengthen students' Arabic skills and the forms of assessment applied at the school. The methodology used is descriptive qualitative, with data collected through in-depth interviews with teachers, language department management, and students proficient in Arabic, along with documentation of the learning materials used. The results show that Arabic language activities at the school include four types of activities: vocabulary enhancement, speaking skills in daily life, lectures, and an intensive Arabic program for new students. These activities significantly support the improvement of students' ability to speak Arabic, focusing on education that supports speaking practice through memorization, reading vocabulary, and speaking in Arabic.